Anatomic Total Shoulder Arthroplasty versus Hemiarthroplasty for Glenohumeral Osteoarthritis: A Systematic Review and Meta-Analysis - Filippo Migliorini (MDPI AG, 2021)
Purpose: Both anatomic total shoulder arthroplasty (TSA) and shoulder hemiarthroplasty (SHA) are used for the management of end-stage glenohumeral osteoarthritis (GHOA). The present study compared TSA and SHA in terms of clinical outcome and complication rate. Methods: This meta-analysis followed the PRISMA guidelines. In October 2021, the following databases were accessed: Web of Science, Google Scholar, Pubmed, Scopus. All clinical trials comparing anatomical TSA versus SHA for GHOA were considered. Results: Data from 11,027 procedures were retrieved. The mean length of the follow-up was 81.8 (16 to 223.20) months. The mean age of the patients was 61.4 ± 8.6 years, and 56.0% (5731 of 10,228 patients) were women. At last follow-up, the age-adjusted constant score was greater following TSA (p < 0.0001), as were active elevation (p < 0.0001), flexion (p < 0.0001), abduction (p < 0.0001), and American Shoulder and Elbow Surgeons Shoulder Score (p < 0.0001). Postoperative pain (p < 0.0001) and revision rate (p = 0.02) were lower in the TSA group. Conclusions: Anatomic TSA performed better than SHA in patients with GHOA.